CircRNA TUBA1C promotes proliferation and glucose metabolism, and blocks apoptosis of osteosarcoma cells through sponging miR-143-3p - Yi-Bing Liu; Wen-Hao Dai; Jun-Jie Chang; Kang Wei (Polish Journal of Pathology)
Osteosarcoma (OS) is a malignant bone tumour that commonly occurs in paediatric and adolescent patients. Currently, effective therapy for OS remains elusive due to poor patient survival rates. In this study, we observed significantly elevated expressions of circTUBA1C in OS tumours and cells. Silencing circTUBA1C effectively suppressed proliferation and glucose metabolism, and promoted apoptosis of OS cells. Furthermore, we discovered that miR-143-3p played a reverse role to circTUBA1C in OS cells. Bioinformatics analysis, RNA pull-down assay, and luciferase assay demonstrated that circTUBA1C acted as a sponge for miR-143-3p, blocking its expression in OS cells. Finally, rescue experiments showed that inhibition of miR-143-3p in circTUBA1C-silenced OS cells significantly overrode the low-circTUBA1C-mediated miR-143-3p upregulation and OS cell progression in vitro and in vivo . Our results demonstrate the critical roles and molecular targets of circTUBA1C in modulating OS progression, suggesting that circTUBA1C inhibition could serve as a new therapeutic strategy for treating OS.